The livestock sector transformation in Ethiopia: the fundamental role of animal identification, registration, data recording and traceability systems - Gebreyohanes, Gebregziabher; Meseret, Selam; Tera, Asrat; Negussie, Enyew; Ojango, Julie M.K.; Chinyere, Ekine; Mrode, Raphael A.; Okeyo Mwai, Ally (2022)
Livestock production in Ethiopia is predominated by extensive production systems where animals graze in communal grazing lands that exposes to disease transmission and indiscriminate breeding. Intensive stall feeding occurs, mostly in peri-urban settings, with cows mainly fed on straw and limited fresh forages. Animal movement within the country for herd replacement poses disease risk due to lack of movement control. Export of live animals and animal products, mostly meat require traceability system which not only able to identify the animal and the premises, where they are raised, but also traces how they left such premises to the ultimate markets. Ethiopia has developed a road map for livestock information system which also requires household, farm, and animal level information. This paper describes and discusses the need for a harmonized national livestock identification, registration, and data recording system, review existing experiences in the country and elsewhere in Eastern Africa, based on which recommendations in the related areas are made. The critical place of animal identification, registration and data recording as the basis for animal and animal product traceability, disease control, genetic improvement of farmers’ animals, annual planning, acquisition of bank loan and insurance are outlined. The need and values of adopting standardized identification system, establish a centralized database, and data capture tools are articulated. In addition, for success, the importance of long-term commitment, at different levels, including the role of both the public and private sectors are emphasized. The role of government in enforcing the related laws and policies, the requisite organizational structure, infrastructure, and human capacity needs are also pointed out. Professional societies like the Ethiopian Society of Animal Production (ESAP), and Ethiopian Veterinary Association (EVA) are platforms to exhaustively discuss and promote establishment and implementation of national system for animal identification, registration, and data capture are underscored.